MXene-Assisted NiFe sulfides for high-performance anion exchange membrane seawater electrolysis - Jiaqi Wang; Yue Liu; Ganceng Yang; Yanqing Jiao; Youming Dong; Chungui Tian; Haijing Yan; Honggang Fu (Nature Communications, 2025)
Abstract Anion exchange membrane seawater electrolysis is vital for future large-scale green hydrogen production, however enduring a huge challenge that lacks high-stable oxygen evolution reaction electrocatalysts. Herein, we report a robust OER electrocatalyst for AEMSE by integrating MXene (Ti3C2) with NiFe sulfides ((Ni,Fe)S2@Ti3C2). The strong interaction between (Ni,Fe)S2 and Ti3C2 induces electron distribution to trigger lattice oxygen mechanism, improving the intrinsic activity, and particularly prohibits the dissolution of Fe species during OER process via the Ti-O-Fe bonding effectively, achieving notable stability. Furthermore, the good retention of sulfates and the abundant groups of Ti3C2 provide effective Cl- resistance. Accordingly, (Ni,Fe)S2@Ti3C2 achieves high OER activity (1.598 V@2 A cm-2) and long-term durability (1000 h) in seawater system. Furthermore, AEMSE with industrial current density (0.5 A cm-2) and durability (500 h) is achieved by (Ni,Fe)S2@Ti3C2 anode and Raney Ni cathode with electrolysis efficiency of 70% and energy consumption of 48.4 kWh kg-1 H2.